Management of vitamin D deficiency in clinical practice: results of a nationwide multidisciplinary study. - Gómez de Tejada Romero, María Jesús; Torregrosa Suau, Óscar; Cancelo Hidalgo, María Jesús; Martínez Díaz-Guerra, Guillermo; Valdés, Carmen; Valdés, Llorca; Tarazona Santabalbina, Francisco José; Etxebarría Foronda, Íñigo; Sosa Henríquez, Manuel (Journal of Osteoporosis & Mineral Metabolism / Revista de Osteoporosis y Metabolismo Mineral (Spanish edition))
Introduction: in recent years, there has been considerable interest in vitamin D, both regarding its physiological aspects and its deficiency, the need for supplementation, recommended doses, and even the type of metabolite that should be used. Material and Methods: given the lack of universally accepted criteria among all scientific societies and the significant heterogeneity observed in clinical practice regarding these issues, we conducted a survey of a sample of 698 doctors in Spain from the specialties of Primary Care, Internal Medicine, Rheumatology, Traumatology, Endocrinology, Gynecology, and Geriatrics to understand their opinions on various aspects of vitamin D management. Results: there is a notable disparity in the responses to the 8 questions related to their usual clinical practice, both in the likelihood of requesting a vitamin D determination and in how it is prescribed. Conclusion: finally, the recommendations of the expert panel that developed the survey and analyzed its results are presented.